(untitled) (Altre Modernità, 2015)
In this article I analyse the Spanish novel Twist by Harkaitz Cano, winner of the 2012 Euskadi prize. In particular, I focus on the different points of view the narrator uses throughout the plot, which reflect the fragmentary situation left by the disappearance of two young men, Soto and Zeberio, who were kidnapped, tortured and killed by rogue elements of the police. Their friend and squeaker, Diego Lazkano, lives a miserable life, tormented by the continuous bites of memory and sense of guilt, which come to the surface of narration through the constant use of flashback and analogies.